Small-molecule compound from AlphaScreen disrupts tau-glycan interface - Faris, Shannon; Jin, Weihua; Gibson, James; Murray, Anqesha; Smith, Nathan; He, Peng; Zhang, Fuming; Linhardt, Robert; Wang, Chunyu (Frontiers in Molecular Biosciences, 2022)
Tauopathies are neurodegenerative diseases characterized by intracellular abnormal tau deposits in the brain. Tau aggregates can propagate from one neuron to another in a prion-like manner, mediated by the interaction between tau and cell surface heparan sulfate (HS) proteoglycans. We developed an AlphaScreen assay, with His-tagged tau and biotinylated heparin, to represent the tau-HS interface to target the tau-glycan interface. Using our AlphaScreen assay, with a Z-factor of 0.65, we screened ~300 compounds and discovered a small-molecule compound (herein referred to as A9), which can disrupt the tau-heparin interaction with micromolar efficacy. A9 also effectively inhibited heparin-induced tau aggregation in Thioflavin T fluorescence assays and attenuated tau internalization by H4 neuroglioma cells. These results strongly suggest that A9 can disrupt the tau-glycan interface in both in vitro molecular and cellular environments. We further determined that A9 interacts with heparin rather than tau and does so with micromolar binding affinity as shown by nuclear magnetic resonance and surface plasmon resonance experiments. A9 binds to heparin in a manner that blocks the sites where tau binds to heparin on the cell surface. These results demonstrate our AlphaScreen method as an effective method for targeting the tau-glycan interface in drug discovery and A9 as a promising lead compound for tauopathies, including Alzheimer’s disease.